Learning Difficulties in Arabic Grammar Instruction: A Qualitative Study in Islamic Secondary Education: Learning Difficulties in Arabic Grammar Instruction: A Qualitative Study in Islamic Secondary Education - Muh. Sabilar Rosyad; Said Fahem (AL-MUARRIB: JOURNAL OF ARABIC EDUCATION, 2026)
The teaching of Arabic grammatical rules remains a significant challenge for students at the madrasah tsanawiyah level and continues to hinder the development of comprehensive Arabic language proficiency. Although numerous studies have addressed challenges in Arabic language learning, systematic investigations that examine learners’ difficulties in Arabic grammar instruction while proposing context-sensitive pedagogical solutions grounded in institutional practice remain limited. This study aims to identify and classify the types of difficulties experienced by eighth-grade students at MTs Mambaus Sholihin Suci in learning Arabic grammar and to formulate instructional strategies to address these challenges. Employing a descriptive qualitative research design, data were collected from students and Arabic grammar teachers through classroom observation, in-depth interviews, and document analysis, with the researcher serving as the primary research instrument. Data trustworthiness was ensured through source triangulation, and the data were analyzed using Miles and Huberman’s interactive analysis model. The findings reveal eight major factors influencing students’ difficulties in Arabic grammar learning: low learning motivation, challenges in grammatical memorization, learning environment, limited instructional time, peer influence, linguistic competence (language skills and language components), teacher competence, and instructional materials. These findings suggest that students’ difficulties can be reduced through adaptive grammar instruction, effective memorization strategies, collaborative learning groups, increased learner self-efficacy and commitment, curriculum alignment, and enhanced teacher professionalism. This study contributes to Arabic language education by providing a pedagogically grounded and context-responsive framework for Arabic grammar instruction in Islamic secondary education.